PENDIDIKAN HOLISTIK SEBAGAI DASAR PEMBENTUKAN KARAKTER - Kasingku, Juwinner; Fellix Gosal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is one of the essential aspects of human life, not only for transferring knowledge but also for shaping character and developing potential in a holistic manner. This article highlights the importance of character education in building individuals who have balanced moral, physical, mental, and spiritual qualities. Character education is a continuous process to develop positive values ​​within individuals, enabling them to live meaningful lives and contribute positively to society. The research method used in this article is qualitative, analyzing recent sources related to the formation of character through appropriate education. Various articles, books, and related documentation are used to support the findings of this research. The analysis shows that holistic education based on spiritual values ​​provides a strong foundation for individuals to face life's challenges, not only in physical and mental aspects but also in moral aspects, and maintain good relationships with their environment. Holistic education plays a crucial role in producing students who are morally and socially intact in global society. By integrating physical, mental, social, and spiritual aspects in the education process, students can be more prepared and capable of addressing various challenges encountered in daily life. Holistic education not only benefits to students but also the surrounding community by creating a more harmonious and cultural environment. Therefore, the implementation of holistic education becomes an urgent necessity in the global education system, in order to produce a generation that is not only academically intelligent but also has high moral standards and the ability to adapt in an increasingly complex and dynamic environment.